Produksi Embrio In Vivo di Balai Embrio Ternak (BET) Cipelang dan Tren Perkembangan Embrio Transfer Global - Irma Irma; Siti Darodjah; Nena Hilmia; Oloan Parlindungan; Ani Rosmayanti; Sri Wahyuni Siswanti; Septaria Jodiansyah; Darlian Fachruddin; Laelatul Choiriyah; Sikin Sikin; Weni Kurniati; Cece Sumantri (Jurnal Ilmiah Fillia Cendekia, 2022)
The development of the global genetic market has change in strategy, large-scale genetic companies, and artificial insemination has driven the industrialization of embryo market. As a result, the demand for embryo production is increasing. The purpose of this report is to briefly explain the current situation of the in vivo embryo production at the Livestock Embryo Centre (LEC), and review the development trends of global embryo transfer. In vivo embryo production data comes from secondary data for 2014-2020 from the LEC, while world transfer embryo development data comes from embryo transfer association. The average of ova (oocyte and embryo) ranged from 7-10 ova/flushing (averages 8 ova) with transferable embryos ranging from 3-5 embryos/flushing (average 4 embryo). Percentage of transferable embryo ranged from 36%-54% (averages 48%). Estimated numbers of ova and transferable embryos per flush in the world were 10.5 and 6.4 in 2019, respectively. In general, the average production of in vivo embryos and transferable embryos at LEC increases every year. Trend of world embryo production increases while in vivo embryo decreased accompanied by an increase in in vitro embryo production.